Analysis of acoustical performance of Bi-layer graphene and graphene-foam-based thermoacoustic sound generating devices. (February 2018) - Lee, Kyoung-Ryul; Jang, Sung Hwan; Jung, Inhwa
Abstract: The objective of this paper is to investigate the acoustical performance of thermoacoustic sound generating devices made of bi-layer graphene and graphene foam. Bi-layer graphene and graphene foam were synthesized using chemical vapor deposition and characterized using HR Raman, X-ray photoelectron spectra, and FE-SEM. The sounds generated by the thermoacoustic devices are measured using a microphone in a semi-anechoic chamber, and frequency spectrums are calculated using a spectrum analyzer. The effects of the input frequency, the voltage of the AC source, and the addition of DC offset on total sound pressure levels have been studied. In particular, the frequency spectra of the generated sounds, which are related to tone quality, are investigated. Compared with the bi-layer graphene thermoacoustic device, the graphene foam thermoacoustic device generated louder sound at low voltage. Additionally, the spectrum of sound generated by the graphene foam thermoacoustic device was clearly different from the spectrum of sound generated by the bi-layer graphene device. The difference in acoustical performance between the thermoacoustic devices made of bi-layer graphene and graphene foam should be considered when developing graphene-based speakers. Graphical abstract: Image 1